Pyelonephritis Therapy in Rats: Random Association with Excreted Urinary Antibacterial Activity - Burrous, S. E. (1970)
In vitro activities or excreted urinary activities of 56 generic and experimental drugs against two organisms commonly associated with human pyelonephritis, Escherichia coli and Proteus mirabilis, are not correlated with the in vivo activities of these compounds as measured by reduction of viable organisms in kidneys in experimental pyelonephritis.